PENILAIAN TINGKAT LAJU EROSI di DAS CISANGGARUNG HULU MENGGUNAKAN METODE USLE - Tri Wahyudin Ahmad; Muhammad Syahril Badri Kusuma; Faizal Immaduddin Wira Rohmat; Arief Yudho Wicaksono; Vika Febriyani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Soil erosion is one of the major environmental degradation processes that directly contribute to land quality deterioration, increased river sedimentation, and disruption of hydrological functions within a watershed. This study aims to spatially model erosion rates in the Upstream Cisanggarung Watershed using the Universal Soil Loss Equation (USLE) integrated with a GIS-based Model Builder to develop an automated, efficient, and reproduceble workflow. The analysis was conducted by incorporating all USLE components (R, K, LS, and CP). Rainfall data, soil type maps, 30 m resolution FABDEM, and land cover maps were employed as the main inputs in the modeling process. The results indicate that erosion rates range from 20.66 to 67.60 ton/ha/years, with a Sediment Delivery Ratio (SDR) of 6.58%. Consequently, the sediment yield reaching the watershed outlet was estimated to range from 60.517,5 to 198.034,6 ton/years. Spatially, erosion hotspots were identified in areas with steep slopes dominated by dryland agriculture and plantation land use. The integration of Model Builder improve data processing consistency, reduce manual errors, and enable rapid data updates for subsequent analyses. These findings underscore the need for implementing conservation strategies such as terracing, contour farming, and vegetative rehabilitation to reduce erosion rates and support sustainable watershed management.